Prof. Ir. Ts. Dr. Ahmad Ziad Sulaiman appointed Deputy Vice Chancellor Academic Affairs and International UMP - Mimi Rabita, Abdul Wahit (2023)
PEKAN, 15 May 2023 - Professor Ir. Ts. Dr. Ahmad Ziad Sulaiman, 46, was appointed the new Deputy Vice-Chancellor (Academic Affairs and International) of Universiti Malaysia Pahang (UMP) effective 15 May 2023.